Headaches, sleep and academic success in adolescents. - Pinto, Teresa Rebelo (2013)
Introduction and Objectives Sleep complaints often correlate with other health and social problems. During a national study about sleep habits in adolescents, we observed a very high frequency of headaches, so the aim of this work was to analyse what could be correlated with this complaint in terms of sleep duration, daytime sleepiness, academic success, age and gender. Materials and Methods We used a specific questionnaire that included Cleveland Adolescent Sleepiness Scale (CASQ) and other variables concerning sleep related habits, sleep complaints, health complaints and demographics. Teachers from 31 schools across Portugal collected data between January and April, 2012. We used SPSS to analyse data. Results The 6838 participants were between 12 and 22 years old, mean=14.97(1.99); 53.3% were females. From the whole sample, 53.8% (3671) students reported having headaches regularly. Those with a headache complaint slept less hours during weekdays (p=0.008) and more hours on weekends (p=0.045); they also had more daytime sleepiness (p=0.000), but showed no differences on academic success (p>0.050). As expected girls had more headaches than boys (p=0.000) and there were no differences across age, since all groups had high frequency of headaches (p=0.098). Conclusions These results suggest that in adolescents headaches are also related to sleep deprivation or sleep problems. In the future, we should pay more attention to headaches as a symptom of sleep problems and explore which factors may mediate the risk of academic failure in the presence of headaches. Furthermore, the high level of headaches in younger people across all age groups supports the need of early intervention.